The Pursuit of Fulfillment: A Phenomenological Study of Street Sweepers in the Philippines - Seclot, Joseph (Social Sciences and Development Review, 2025)
Street sweepers are one of the most vulnerable groups of workers nowadays due to their working conditions, tenure of employment, health issues, and socio-economic status. Nevertheless, they are the driving force behind the maintenance of solid waste management and the cleanliness of cities.  Using the Self-Determination Theory as the framework of this study, this paper aims to explore the sense of fulfillment experienced by street sweepers in Tangub City, Misamis Occidental. Using phenomenological research design, eight (8) street sweepers were interviewed using a semi-structured interview guide questionnaire. The gathered data were transcribed, validated, and analyzed using the Braun and Clarke thematic analysis approach. Results revealed four (4) emerging themes: maintaining community cleanliness and orderliness, upholding professional integrity and work ethic, being acknowledged and respected in the community, and supporting family livelihood and well-being. In conclusion, the sense of fulfillment of street sweepers is driven by their sense of orientation, commitment, and accountability, how the community values them, and how the work sustains the physiological needs of their families. The city government should recognize the invaluable contributions of street sweepers by ensuring fair wages, benefits, job security, and recognition initiatives, which can foster greater motivation and job satisfaction. Future research could explore ways to improve job security and benefits for workers in similar sectors, ensuring their efforts are recognized and adequately rewarded.
Keywords: Fulfillment; Happiness; Phenomenological Study; Satisfaction; Street Sweepers